2014
DOI: 10.22260/isarc2014/0026
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption of Building Information Modeling in the Design Organization: An Empirical Study of Architects inKorean Design Firms

Abstract: Recently, Building Information Modeling (BIM) technology has attracted much attention in the Architecture, Engineering, and Construction (AEC) industry. Despite the growing interest in BIM technology, the benefits of BIM have not yet been fully realized during the course of implementation of BIM because of its low adoption rate among architects. Therefore, it is significant important in successful adoption of BIM in design organizations, understanding of the factors influencing the adoption of BIM. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…In BIM model formulation, previous research of [48] infused the constructs of unified technology acceptance and use theory (UTAUT) into technology acceptance models (TAM) with two insignificant scales. [57] extend TAM to include computer self-efficacy, top management support, technical support, training and compatibility with two out of nine hypotheses significant. [49] combined TAM and innovation diffusion theory (IDT) with all 13 hypotheses significant.…”
Section: Resultsmentioning
confidence: 99%
“…In BIM model formulation, previous research of [48] infused the constructs of unified technology acceptance and use theory (UTAUT) into technology acceptance models (TAM) with two insignificant scales. [57] extend TAM to include computer self-efficacy, top management support, technical support, training and compatibility with two out of nine hypotheses significant. [49] combined TAM and innovation diffusion theory (IDT) with all 13 hypotheses significant.…”
Section: Resultsmentioning
confidence: 99%
“…A random sampling frame to collect data from a subset forming a representative data for the group was used (De-Vaus, 2002). Sample frames from previous research in IT and BIM were studied, and a frame was developed covering medium to large construction organisations in addition to CIDB Class-A contractors (Son et al, 2012;Lowry, 2002;Peansupap and Walker, 2005;Davis and Songer, 2008;Jacobsson and Linderoth, 2012;Peansupap and Walker, 2006;Miller, Radcliffe and Isokangas, 2009;Brewer and Gajendram, 2011;Samuelson, 2011;Davies and Harty, 2013;Son et al, 2014;Xu, Feng and Li, 2014). The previously mentioned studies possessed an average sample size of 255 respondents and Hair et al (2010) specified a minimum sample size of 200 for structural equation modelling (SEM).…”
Section: Methodsmentioning
confidence: 99%
“…The outcomes of the study showed that users in the US had higher adoption level for BIM than Korea and the two countries have different mechanisms for BIM acceptance. In another study, Son et al (2014) found that there is a lack of realization of the expected benefits of BIM and examined the factors that can ease BIM adoption for architects. The outcomes of this technology acceptance study showed factors such as subjective norm, compatibility, and computer self-efficacy could influence the behavioral intentions for architects to BIM adoption.…”
Section: Perceived Enjoyment (Enj)mentioning
confidence: 99%
“…Moreover, there has been no study that investigated how the construction industry is accepting and adopting BIM-AR integration within their processes. There have been various studies that investigated BIM solely Son et al,2014) or AR (tom Dieck et al, 2018 andLeue et al, 2014) acceptance and adoption individually but not their integrated BIM-AR acceptance in the construction industry. Hence, this study aims to fill this knowledge gap by developing a Technology Acceptance Model (TAM) based on the integration of BIM-AR.…”
Section: Introductionmentioning
confidence: 99%